2011
DOI: 10.2215/cjn.02200311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dialysis Modality on Survival of Hepatitis C-Infected ESRF Patients

Abstract: SummaryBackground and objectives Hepatitis C virus (HCV) infection is associated with increased mortality and morbidity in end-stage renal failure (ESRF) patients. Despite a lower incidence and risk of transmission of HCV infection with peritoneal dialysis (PD), the optimal dialysis modality for HCV-infected ESRF patients is not known. The aim of this study was to evaluate the impact of dialysis modality on the survival of HCV-infected ESRF patients. Design, setting, participants, & measurementsThe study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Several other studies have reported that an extremely low anti-viral treatment proportion in dialysis patients with HCV infection, 13 , 17 which is similar to our findings. Our data suggested that in HCV-infected ESRD patients, receiving HD or PD had similar risks of mortality; which is consistent with the report by Bose et al 18 …”
Section: Discussionsupporting
confidence: 93%
“…Several other studies have reported that an extremely low anti-viral treatment proportion in dialysis patients with HCV infection, 13 , 17 which is similar to our findings. Our data suggested that in HCV-infected ESRD patients, receiving HD or PD had similar risks of mortality; which is consistent with the report by Bose et al 18 …”
Section: Discussionsupporting
confidence: 93%
“…The adverse and independent effect of HCV on cardiovascular mortality after renal transplantation has been also noted [25]. Bose et al [31] found that coronary artery disease played an independent and significant role on all-cause mortality in a large cohort of HCV-infected end-stage renal failure patients. Oyake et al [32] prospectively measured aortic stiffness in 94 dialysis patients and observed that HCV viraemia was per se associated with high pulse-wave velocimeter measurements.…”
Section: Discussionmentioning
confidence: 80%
“…Bose et al. [31] found that coronary artery disease played an independent and significant role on all‐cause mortality in a large cohort of HCV‐infected end‐stage renal failure patients. Oyake et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bose et al . analyzed a large cohort of HCV-infected individuals ( n =424) treated with haemodialysis ( n =290) and peritoneal dialysis ( n =134) in Australia and New Zealand over the period 1994-2008, and found that coronary artery disease (CAD) was an independent risk factor for mortality, 1.75 (1.34 to 2.30), P <0.01 [17]. Butt et al .…”
Section: Hcv and Cardiovascular Mortality Risk In Dialysis Populationmentioning
confidence: 99%